2005
DOI: 10.1176/jnp.17.4.496
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Stages of Huntington’s Disease

Abstract: Individuals with manifest Huntington's disease (HD) were interviewed with regard to the presence, frequency, and severity of depression symptoms to better characterize depressed mood across the disease course in HD. Rates of depression were more than twice that found in the general population. One-half reported that they had sought treatment for depression, and more than 10% reported having at least one suicide attempt. The proportion of HD patients endorsing significant depression diminished with disease prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(80 citation statements)
references
References 40 publications
0
78
1
1
Order By: Relevance
“…From the HD literature that has addressed disease stage, there are mixed results regarding critical periods for anxiety and depression, but suggest they do not necessarily follow a linear trend across disease stage[9, [12][13][14]. One large study revealed a significant peak in anxiety and depression symptoms at Stage 2 of the disease, while the authors of a more recent study found prevalence of moderate to severe depression to be highest among stages 4-5[9].…”
Section: Introductionmentioning
confidence: 99%
“…From the HD literature that has addressed disease stage, there are mixed results regarding critical periods for anxiety and depression, but suggest they do not necessarily follow a linear trend across disease stage[9, [12][13][14]. One large study revealed a significant peak in anxiety and depression symptoms at Stage 2 of the disease, while the authors of a more recent study found prevalence of moderate to severe depression to be highest among stages 4-5[9].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical diagnosis of HD is determined on the basis of motor symptoms; however, the pre-motor stages of the disease are commonly associated with psychiatric manifestations including depression (Paulsen et al, 2005;Duff et al, 2007;Julien et al, 2007;Marshall et al, 2007). Depression is one of the most prevalent causes of disability worldwide and is diagnosed in women more frequently than in men (Fava and Kendler, 2000;Kornstein et al, 2000;Marcus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This data can be justified, according to literature, as a neuropsychiatric symptom unrelated to cognitive or motor deficits and may have as a predictor anxiety 16,[23][24][25] .…”
Section: Discussionmentioning
confidence: 86%
“…Anxiety was also one of the changes often mentioned by caregivers and is pointed as a major cause of problems in interpersonal relationships of individuals with HD and their caregivers 9,15,22,23 .…”
Section: Discussionmentioning
confidence: 99%